Clinical characteristics of multiple sclerosis in Västerbotten County in northern Sweden. Issue 5 (16th April 2004) - Sundström, P; Svenningsson, A; Nyström, L; Forsgren, L
Abstract : Background: Most clinical data for multiple sclerosis are hospital based—that is, derived from patients referred to clinics specialising in the disease. Objectives: To present data derived from two population based multiple sclerosis populations, an incidence cohort and a prevalence population, from Västerbotten County, northern Sweden. Methods: The two populations were identified from multiple sources, and case ascertainment was assured through a personal clinical review, including interviews and examination of the patients. Results: Characteristics at onset for the different clinical subtypes of multiple sclerosis are presented, including the clinical spectrum of the first attack, the anatomical correlation between the first and second attacks, sex distribution, and disability distribution. Conclusions: Based on the comparison of present and earlier natural history data, multiple sclerosis appears to be a slightly more benign disease than previously recognised.